BPM Capability Development - A Matter of Contingencies - Niehaves, Björn; Pöppelbuß, Jens; Plattfaut, Ralf; Becker, Jörg (Business Process Management Journal, 2014)
Purpose - Business process management (BPM) is a key concept in information systems (IS) research that helps to connect business strategy with the use of technology in an organization. Contemporary BPM research is no longer only about methods, procedures, or tools for managing or modeling processes but about assessing and developing BPM capability in organizations. For this purpose, a vast collection of maturity models has been designed by practitioners and scholars alike. Such models are used to assess the status quo and benchmark it against other organizations, and, most important, to guide the development of BPM capability. With this study, the paper challenges the maturity model perspective of such development models. Design/methodology/approach - In this study, methods of qualitative IS research are employed to address the research objectives. Findings - The paper shows that maturity model-based guidance would be inadequate. Instead, other concept-external factors resulting from organizational and environmental characteristics appear to be important indicators. The theory discussion introduces alternative takes on BPM capability development, lays out implications for BPM practice, and presents potentially fruitful paths for future research in the area of BPM capability development. Originality/value - This paper challenges the current perspectives and contributes a new direction for conceptualizing BPM capability development.
Keywords: Business process management; Capability development; Case study; Contingency theory; Dynamic capabilities; Maturity model